Western Australia’s Inventory of Abandoned Mine Sites - Strickland, C.D.; Ormsby, W.R. (Mine Closure 2006: Proceedings of the First International Seminar on Mine Closure, 2006)
Mining has occurred in Western Australia for more than 150 years, resulting in many thousands of workings that were abandoned after exploration or mining (Figure 1). Until recently, few of these workings and other associated mine site features were documented. The Geological Survey of Western Australia (GSWA) commenced a program to accurately locate and document abandoned mine sites throughout the State in 1999. The inventory of individual mining-related features such as shafts, open cuts, dumps and infrastructure focuses upon sites that are close to towns and main roads and were in production before 1990, when new environmental legislation took effect. The innovative use of hand-held personal computers (PC) and Global Positioning System (GPS) technology has facilitated the collection of a great deal of field data. This paper discusses the background, methodology, and progress of the inventory, and applications of the database.